Bolivian mas-ipsp, halfway between a social movement and a political party (2008)
The article reports a research about the organizational and political nature of “Movimiento al Socialismo – Instrumento Político por la Soberanía de los Pueblos (MAS-IPSP)” in Bolivia. It begins the study with a description of the creational conditions of the MA-IPSP, in the hope of distinguishing in it the operation of a political party in the long term. Then the article examines the party’s orientation as a political instrument and finally analyzes the successes and turns of Evo Morales’ victory inside the organization.